Evidence-based uncertainty analysis: What should we now do in Europe? A view point. Issue 5 (4th May 2021) - Lofstedt, Ragnar; Bouder, Frederic
Abstract : There has been a great deal of discussion regarding both the communication of scientific uncertainties associated with regulatory decisions as well as the supposed need for more transparent uncertainty analyses associated with risk assessments themselves. More recently, in Europe this discussion has been led by the European Food Safety Authority's Scientific Committee. In this viewpoint, we both review the ongoing debates surrounding uncertainty analysis as well as discuss some of the problems associated with communicating uncertainties. In the final section of the viewpoint, we offer some recommendations regarding what EFSA could do now going forward.